Spatial Heterogeneity of Long-Term Sandy Shoreline Change Along Eastern Hainan Island, China (1987–2025) - Yuanting Ding; Yi Liu; Qiyi Du; Jitao Yu (Journal of Marine Science and Engineering, 2026)
Long-term shoreline change on tropical islands is spatially heterogeneous, but alongshore contrasts remain insufficiently resolved. We quantified shoreline change along the 151.1 km eastern sandy coast of Hainan Island, China, from 1987 to 2025 using Landsat-derived visually interpreted shoreline proxies and the Digital Shoreline Analysis System across 1413 transects. The coast was broadly stable to accretional, with a mean linear regression rate (LRR) of 0.49 m/yr and a mean net shoreline movement (NSM) of 17.72 m. Under the uncertainty-aware classification, 28.0% of transects were stable, 42.1% accretional, 8.2% erosional, and 21.7% indeterminate. For descriptive comparison, the eight sectors were grouped into three broad alongshore zones: a stable northern zone (Beaches A–B), an accretion-dominated central zone (Beaches C–E), and a heterogeneous southern zone (Beaches F–H). The strongest accretion occurred at Beach D (LRR = 7.63 m/yr), whereas the strongest erosion occurred south of the offshore artificial island at Beach F (LRR = −3.97 m/yr). These contrasts show that coast-wide stability or accretion can mask localized erosion. The observed patterns were spatially associated with differences in headland-bay morphology, nearshore seagrass beds, engineering structures, estuarine processes, and lagoon-inlet settings. The findings support beach-sector monitoring and differentiated coastal management.

Three-dimensional spherical ordered mesoporous Al-MCM-48 solid acid catalysts for the rapid conversion of biomass-derived GVL to butene - Haibiao Yu; Yudong Li; Yuanting Du; Ruixi Yang; Weijun Shan; Yuejiao Wang; Ruan Chi; Ying Xiong (Fuel, 2026)

Aluminum modified MCM-41 solid acids catalyst with large surface area for efficiently catalyzing biomass-derived GVL decarboxylation to butene - Ying Xiong; Yushan Jia; Yuanting Du; Xinwei Du; Xiaogeng Feng; Weijun Shan; Haibiao Yu (Fuel, 2025)

Dy and K double-additive modified Co3O4 catalyst with high resistance to NO for catalyzing N2O decomposition - Haibiao Yu; Yanan Li; Yan Pan; Yuanting Du; Xiaogeng Feng; Junshuo Cui; Zhenning Lou; Weijun Shan; Ying Xiong (Chemical Engineering Journal, 2025)

Transcriptome analysis of the genes and regulators involving in vitamin E biosynthesis in Elaeagnus mollis diels - Shuhui Du; Yuanting Guo; Qianqian Li; Xiaoyan Hu; Yang Tian; Baochang Cheng; Shengji Wang; Zhiling Wang; Ruifen Ren; Zhaoshan Wang (Plant Molecular Biology, 2024)

Deciphering the stability mechanism of Pt-Ni/Al2O3 catalysts in syngas production via DRM - Rui Zhao; Kun Cao; Rongli Ye; Yuanting Tang; Chun Du; Fudong Liu; Yunkun Zhao; Rong Chen; Bin Shan (Chemical Engineering Journal, 2024)